Pro-health behavior of Łęczna town residents concerning protection against UV radiation - Karwacka, Lidia; Kamińska, Aneta; Wójcik, Dorota; Szabelska, Anna; Batkowska, Justyna; Borowicz, Janusz; Szalewski, Leszek (Polish Journal of Public Health, 2016)
Introduction. The fashion for a tan appeared at the beginning of the twentieth century, in the era of technological progress and urbanization with medical knowledge about heliotherapy and the promotion of the tan by fashion designer Coco Chanel being a contributing factor in it. The International Agency for Research on Cancer classified the UV to the first group of carcinogens but despite these warnings the increase in exposure to UV radiation has been seen in recent years. New solariums have been created around the world so that people can enjoy a tan all year round, no matter what the weather conditions are. Aim. The aim of the study was to assess the attitudes and behaviors related to UV radiation exposure among residents of Łęczna. Material and methods. A survey conducted among 180 people inquiring about sociodemographic characteristics and attitudes and behaviours associated with exposure to UV radiation while tanning. Results. Statistical analysis of the data obtained in the study showed that the socio- demographic characteristics affect the attitudes and behaviour associated with exposure to UV radiation. Suntan is believed to be significantly more fashionable among women, people with secondary education who have no permanent relationships. Conclusion. There is a need for preventive actions and educational programs concerning the dangers of UV radiation in order to develop not only knowledge but also the correct behaviour in society.